(untitled) (Conferencea, 2022)
Theoretical foundations, stages, driving forces, efficiency factors of modern digitalization and the digital economy are considered. The key components of the term "digital economy" are presented: digital technologies, ecosystems and transformations, taking into account their interconnection and interdependence.